A short discussion about "Economic optimization design of shell-and-tube heat exchangers by a cuckoo-search-algorithm". (5th February 2015) - Fister, Iztok; Fister, Iztok; Yang, Xin-She
Abstract: This short discussion concerns some inaccuracy in the recently published paper "M. Asadi et al. Economic optimization design of shell-and-tube heat exchangers by a cuckoo-search-algorithm. Applied thermal engineering, 2014". There was a mix-up between the cuckoo search (CS) with the cuckoo optimization algorithm (COA), which may cause further confusion if uncorrected. In this discussion, we intend to clarify the differences between both algorithms so as to provide a more accurate description of both algorithms.